Analysis of Damage Handling in The PT Petrokimia Gresik Factory Conveyor Safety System Using The Naive Bayes Method: Analisa Penanganan Kerusakan Pada Sistem Pengaman Konveyor Pabrik PT Petrokimia Gresik Menggunakan Metode Naive Bayes - Alkhaqiqi, Fashoma Yudha Anggana; Irawan, Denny (Muhammadiyah University, Sidoarjo, 2024)
In the industrial world, the speed of the production process plays a very important role in influencing industrial profits. One of the factors that determines production speed is the conveyor. PT. Petrokimia Gresik is one of the industries that uses conveyors, which pays great attention to accuracy and control of material speed. The function of the conveyor is to send raw materials from PT Petrokimia Gresik fertilizer to be processed. Three safety devices are installed on this tool, namely the low speed switch, outlying belt and cable pull switch. However, this complex security system makes it difficult for field technicians to handle conveyor problems. Problems that occur with conveyors, especially in the electrical and instrumentation parts, are sometimes difficult to find. Therefore, the author had the idea to conduct research related to conveyor problem solving analysis using the naive Bayes classification method. The results of the calculation between naive Bayes calculations and expert opinion show 100% agreement, which is an optimal result. It is hoped that these results can help field technicians in diagnosing and resolving problems when problems occur with conveyors.